Who's to blame?: elaborating the role of attributions in general strain theory - Hoffmann, John P. (Western criminology review, 2010)
Agnew’s general strain theory (GST) has motivated dozens of criminological studies over the past two decades. Borrowing in part from Cloward and Ohlin’s model of delinquency, Agnew claimed that anger, a key component of GST, occurs when adolescents externalize blame for their adversity. This implies that adolescents who blame strain on an external causal agent (e.g., a parent, a teacher, economic disadvantages) are more likely to get angry and thus lash out through delinquent acts. However, this essential characteristic has been largely neglected in studies of GST. The purpose of this article is to show that external attributions of blame remain a fundamental moderator of GST and to elaborate how it affects the association between strain and delinquency. In particular, we draw from research on attribution theory and hostile attribution biases (HAB) to argue that understanding how adolescents interpret adversity is essential to GST